Screening for Cerebral Visual Impairment: Value of a CVI Questionnaire - Ortibus, E.; Laenen, A.; Verhoeven, J.; De Cock, P.; Casteels, I.; Schoolmeesters, B.; Buyck, A.; Lagae, L. (Neuropediatrics, 2011)
The objective of the study was to investigate the screening utility of a questionnaire for cerebral visual impairment (CVI) by correlating the questionnaire with diagnostic tools such as the L94, the Test of Visual Perceptual Skills - Revised and the Visual Perception subtask of the Beery test of VisuoMotor Integration.The questionnaire consisted of 46 items, exploring different characteristics of CVI. We consecutively recruited 91 children. Parents filled out the questionnaire after which all children were seen for a diagnostic evaluation of CVI.There were 58 boys. Subjects’ mean age was 6.10 years. A median of 12 items was ticked in the 45 children with CVI and 7 in the children without impairment. The domain ‘visual attitude’ scored positive most frequently. A logistic regression model using individual items, yielded Receiver Operating Curves for the questionnaire with good areas under the curve of 0.81 against the L94, 0.78 against the TVPS-R and 0.84 against the VP subtask. The sum score of the 6 domains was found to be an easy-obtainable score with a good sensitivity and specificity profile.This CVI questionnaire is a viable tool that has the potential of being implemented as part of a routine screening procedure for CVI.
Keywords: CVI; questionnaire; screening; CP; preterm